$SU(5)_{L} × U(1)_{Y}$ electroweak unification. (17th September 2021) - Palcu, Adrian
Abstract: We propose here—for the first time in the literature, to our best knowledge—an electroweak unification based on the $SU(5)_{L}× U(1)_{Y}$ gauge group. The spontaneous symmetry breaking takes place in the manner $SU(5)_{L}× U(1)_{Y} → U(1)_{em}$, due to a particular Higgs sector consisting of five scalar quintuplets. Each scalar quintuplet acquires its own vacuum expectation value, by means of a proper parametrization which is worked out once an overall vacuum expectation value in the model is established. The decoupling of the low-energy regime (corresponding to the Standard Model) from the high scale (required by our model here) is straightforwardly achieved in order to preserve the consistency with the present experimental data. Finally, a promising phenomenological outcome is derived by simply tuning a single free parameter. Our results also include, besides a viable one-parameter mass spectrum, the prediction of precisely three generations in the fermion sector and the electric charge quantization.